Do Privatizations Boost Household Shareholding? Evidence from Italy - Adolfo Di Carluccio; Giovanni Ferri; Cecilia Frale; Ottavio Ricchi (Fondazione Eni Enrico Mattei (FEEM), 2004)
It is believed that privatizations substantially contributed to boost stock markets through the 1980s and 1990s. However, trough which channels did that materialize? We test whether privatizations improving households' acquaintance with the risk and return characteristics of stocks through the massive accompanying advertising campaigns boosted demand for stocks by enlarging the set of households willing to invest in shares. We use a unique micro-data set collected for a large sample of Italian households on Public Offerings (PO) during 1995-99, the climax of privatizations in Italy. We show that advertising increased the notoriety of the incoming PO at households, and through this furthered households' propensity to subscribe that PO. Furthermore, the propensity to subscribe the incoming PO also increased as households became better informed about past privatizations. Thus, privatizations expanded households' share participation in Italy.
Keywords: D14; D82; E44; G11; 330; Household portfolio choice; Information; Privatizations; Aktionäre; Privater Haushalt; Privatisierung; Italien